(untitled) - Khan, R A (Oxford, 2006)
The book has been planned and desgined for a one-semester course on software quality assurance as a follow up course on software engineering. It is aimed to fit in the undergraduate programme in computer science and master' s program in computer applications being conducted by most of the higher educational institutions
Keywords: computer software; quality control